All we ever wanted : a novel - Giffin, Emily (New York : Ballantine Books, 2018)
"In the new novel from the #1 New York Times bestselling author of First Comes Love and Something Borrowed, a woman is forced to choose between her family and her most deeply held values. Nina Browning is living the good life after marrying into Nashville's elite. Her husband's tech business is booming, and her adored son, Finch, is bound for Princeton. Tom Volpe is a single dad working multiple jobs. His adored daughter, Lyla, attends Nashville's most prestigious private school on a scholarship. But amid the wealth and privilege, Lyla doesn't always fit in. Then one devastating photo changes everything. Finch snaps a picture of Lyla passed out at a party, adds a provocative caption, and sends it to a few friends. The photo spreads like wildfire, and before long, an already divided community is buzzing with scandal and assigning blame. In the middle of it all, Nina finds herself relating more to Tom's reaction than her own husband's--and facing an impossible choice"--
Keywords: Married women -- Fiction; Single fathers -- Fiction; Teenagers -- Fiction; FICTION / Contemporary Women; FICTION / Romance / Contemporary; FICTION / Literary; Domestic fiction